Pelatihan Pembuatan Nata de Coco pada PKK di Tasikmadu, Lowokwaru, Kota Malang - Ulfah Utami; Liliek Harianie; Nur Kusmiyati; Prilya Dewi Fitriasari (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING ON MAKING NATA DE COCO FOR PKK ORGANISATION IN TASIKMADU, LOWOKWARU, MALANG CITY. One of the functional food products is nata. Nata is a collection of cellulose which has a chewy texture, white, producing gel sheets that float on the liquid surface. Material that is often used as a medium for making nata is coconut water, known as Nata de Coco. Acetobacter xylinum bacteria are added in the process of making nata de coco on steril condition. The process is important to be informed to the community, in particular the PKK organization through community development program. The methods used include lectures, practice and evaluation. Survey of partners showed that 23,8% had known the process of making nata de coco while 76,2% had not known the process, through this training, 68% partners strongly agree nata production is used as a business idea.